1986
DOI: 10.1111/j.2044-835x.1986.tb01032.x
|View full text |Cite
|
Sign up to set email alerts
|

Latent inhibition: A developmental study

Abstract: Two latent inhibition experiments were conducted with children aged between 4.6 and 11.8 years. Experiment I sampled a middle socio‐economic class population. Within each age, there were four experimental groups which varied in the number of pre‐exposures to the stimulus that was later used as the reinforced stimulus in a discrimination learning test. Latent inhibition, i.e. poorer learning in the group pre‐exposed to the stimulus as compared with the non‐pre‐exposed group, was found to decrease with age. In E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0

Year Published

1988
1988
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(35 citation statements)
references
References 8 publications
2
33
0
Order By: Relevance
“…This is the case in all of the visual studies that report LI (see Lubow, 1989). Those studies that have failed to get LI with masking (older children in Kaniel & Lubow, 1986, and in the present study) display the masking task in such a way that the subject must scan across the to-be-target stimulus. Preliminary data from our laboratory also suggests that the relative position of the masking task stimuli and the to-be-target stimulus is important in determining whether or not one obtains LI.…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…This is the case in all of the visual studies that report LI (see Lubow, 1989). Those studies that have failed to get LI with masking (older children in Kaniel & Lubow, 1986, and in the present study) display the masking task in such a way that the subject must scan across the to-be-target stimulus. Preliminary data from our laboratory also suggests that the relative position of the masking task stimuli and the to-be-target stimulus is important in determining whether or not one obtains LI.…”
Section: Discussionmentioning
confidence: 71%
“…The apparatus, with the exception of the addition of a timing circuit for measuring response time, was the same as that used by Kaniel and Lubow (1986). The box for presenting stimulus cards was 43 X 29 X 10 cm.…”
Section: Apparatusmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, it has been reported that blocking is not disrupted by amphetamine (Gray, Pickering, Gray, Jones, Abraham, 6 Hemsley, 1997), but the preexposure effect is (Gray, Pickering, Hemsley, Dawling, 6 Gray, 1992). As another example, it has been reported that blocking is weaker in young children than in adults (e.g., Lyczak 6 Tighe, 1975), but the preexposure effect is exhibited by children even without a masking task (e.g., Kaniel 6 Lubow, 1986). As another example, it has been reported that blocking is weaker in young children than in adults (e.g., Lyczak 6 Tighe, 1975), but the preexposure effect is exhibited by children even without a masking task (e.g., Kaniel 6 Lubow, 1986).…”
Section: The Pre-exposure Effect Is a Case Of Attenuation After Blockingmentioning
confidence: 99%
“…). For example, Kaniel and Lubow had NPE children complete a discrimination task with cards displaying pictures of animals and plants, where the correct response was always the image of a plant at the top (a marble and verbal feedback were the rewards for younger and older children, respectively). The PE group did the same task but saw either images of small and large black or white squares (counterbalanced across groups) in the center of the cards.…”
Section: Internal Factorsmentioning
confidence: 99%